Somatotype of top-level serbian rhythmic gymnasts - Purenovic-Ivanovic, T.; Popovic, R. (Journal of Human Kinetics, 2014)
Body size and build influence performance in many sports, especially in those belonging to the group of female aesthetic sports (rhythmic gymnastics, artistic gymnastics, and figure skating). These sports pose high specific demands upon the functional, energy, motor and psychological capacities of athletes, but also upon the size, body build and composition of the performers, particularly of the top-level female athletes. The study of the top athletes (rhythmic gymnasts, in this case) may provide valuable information on the morphological requirements for achieving success in this sport. Therefore, the main objective of this research was to analyze the somatotype of 40 Serbian top-level rhythmic gymnasts, aged 13.04±2.79, and to form the five age group categories. The anthropometric variables included body height, body mass, the selected diameters, girths and skinfolds, and the Heath-Carter anthropometric somatotype. All of the anthropometric data were collected according to International Biological Programme, and then processed in the Somatotype 1.2. The applied analysis of variance indicated an increase in endomorphic component with age. The obtained results show that the balanced ectomorph is a dominant somatotype, being similar for all of the athletes that took part in the research (3.54-3.24-4.5). These results are in line with the ones obtained in previous studies.